Is It Possible for Audit Quality to Impact Tax Aggressiveness? - Pratomo, Dudi; Wibowo , Muhammad Rofik (AKRUAL: Jurnal Akuntansi, 2024)
Introduction/Main Objectives: This study aims to compare the audit fɛes, audit duration, and tax aggrɛssiveness of public accounting firms in the food and beverage subsector listed on the Indonesia Stock Exchange. Background Problems: The firm’s management pays more attention to taxes to maximize profit while minimizing its tax liabilities. Company management may execute tax planning tactics in a legal manner (tax avoidance) or a criminal manner (tax evasion). However, remember that the state suffers because one of the critical sources of governmental funding is diminished. Research Methods: Methods of study include panel data regression analysis and purposeful sampling. The annual report is available online at the company’s and Indonesia Stock Exchange websites. Sixty samples were taken from as many as twelve different companies over a five-year period. Finding/Results: The results showed that combining KAP size, audit duration, and audit costs impacts tax aggressiveness. To a lesser extent than audit time and KAP size, audit fees influence tax aggression for food and beverage companies listed on the Indonesia Stock Exchange between 2017 and 2021. Conclusion: A company in the food and beverage subsector listed on the Indonesía Stock Exchange between 2017 and 2021 may be more or less tax aggressive depending on factors including the size of the public accounting firms, the length of time they have audited the business, and the amount of audit fees paid.